Bahasa Inggris - Tri Widarti; Yatmi; Ian Fii Barril Hidayah; Miftachul Mahmud; Farida Ilmiasari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The phenomena of the sky and the cosmos in the Qur'an are not merely present as symbolic or illustrative objects, but rather are epistemic entities that encourage humans to reflect, understand, and deeply feel the presence of God. In the Islamic tradition, the cosmos is known as kitāb manẓūr (the unfolded book), which is the epistemological counterpart of the Qur'an as kitāb manẓūl (the revealed book). The relationship between the two opens up space for an interpretive approach that is not only text-based, but also based on experience and direct contemplation of the universe. This study aims to examine and formulate a model of cosmic amali interpretation, namely an interpretive model based on the contemplative experience of celestial phenomena as a form of appreciation of cosmological verses in the Qur'an. This study uses a qualitative-hermeneutic approach with thematic analysis techniques on the verses of the Qur'an, accompanied by a literature study of classical and contemporary exegetical works, as well as Islamic philosophy. The research results show that cosmic practical interpretation can be constructed through four stages: sensory observation of the sky, rational reflection comparing observations with revelation, spiritual integration with divine values, and the formation of ethical and ecological awareness. This model offers a new approach to the study of thematic interpretation that emphasizes existential and participatory dimensions, where the subject of interpretation not only understands God's verses textually but also internalizes them in a transcendent cosmic experience.